Implementation of Allocation of Village Funds (ADD) Increases Institutional and Ngombakan Village Development Programs Manifest Good Governance - Taufiqurokhman Taufiqurokhman; Andriansyah Andriansyah (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
The purpose of writing is to determine the implementation of village fund allocation in rural development towards clean village governance (Good Governance: accountability, transparency and participation) starting from the planning stage, transparency and accountability. The study used a qualitative descriptive method with case studies, describing the implementation of Village Fund Allocation Management (ADD) for development in Ngombakan Village. Then compared with the applicable regulations (Permendagri No. 113 of 2014) and cross-check with the real phenomena that occur in the management of Village Fund Allocation (ADD) in Ngombakan village in realizing good governance, so that conclusions can be drawn. The results of this study indicate that the management of ADD in the village of Ngombakan in general has been accountable, transparent and participatory. However, there are still technical problems. These constraints are a constraint from the regency that is late in making a Regent's Regulations regarding the regulations on ADD and its management. This results in delays in reporting related to the management of ADD in the Ngombakan village.